2021
DOI: 10.1093/jas/skab017
|View full text |Cite
|
Sign up to set email alerts
|

The use of live yeast to increase intake and performance of cattle receiving low-quality tropical forages

Abstract: The objective was to evaluate the effects of a specific strain of live yeast (LY) on growth performance, fermentation parameters, feed efficiency and bacterial communities in the rumen of growing cattle fed low-quality hay. In experiment (Exp) 1, twelve Droughtmaster bull calves (270 kg ± 7.6 kg initial BW) were blocked by BW into two groups, allocated individually in pens, and fed ad libitum Rhodes grass hay (8.4% of crude protein [CP]), and 300 g/bull of supplement (52% CP) without (Control) or with LY (8 x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The Verrucomicrobia family RFP12 was found to be prevalent in the rumen of high methane yielding animals [58]. In a recent trial in beef cattle fed a high forage diet [59], the same strain of S. cerevisiae that we used also had an impact on Verrucomicrobia, with a decrease in the relative abundance of this phylum. However, further work is needed, such as methane and H 2 quantifications, to explain the effects of SC supplementation on these taxa.…”
Section: What Was the Impact Of Parturition On Oxidative And Metabolic Status Of The Control Ewes?mentioning
confidence: 83%
“…The Verrucomicrobia family RFP12 was found to be prevalent in the rumen of high methane yielding animals [58]. In a recent trial in beef cattle fed a high forage diet [59], the same strain of S. cerevisiae that we used also had an impact on Verrucomicrobia, with a decrease in the relative abundance of this phylum. However, further work is needed, such as methane and H 2 quantifications, to explain the effects of SC supplementation on these taxa.…”
Section: What Was the Impact Of Parturition On Oxidative And Metabolic Status Of The Control Ewes?mentioning
confidence: 83%
“…In general, their diet is based on grasses and leaves found in different places, especially in flooded areas. Supplementing cattle with specific strains of live yeasts has resulted in increased digestibility of (mainly low quality) fiber ( 10 , 11 ) and increases in dry matter consumption ( 12 , 13 ). Furthermore, Chaucheyras-Durand et al ( 7 ), reported that the main beneficial effect of live yeasts with regards to fiber digestibility is the ability of living yeast cells to reduce ruminal oxygen, which improves the ruminal environment and allows other microorganisms to colonize the rumen and digest fiber.…”
Section: Introductionmentioning
confidence: 99%